2006
DOI: 10.3168/jds.s0022-0302(06)72236-6
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of 1% l-Glutamine to Milk Replacer Does Not Overcome the Growth Depression in Calves Caused by Soy Protein Concentrate

Abstract: Glutamine, an important fuel and biosynthetic precursor in intestinal epithelial cells, helps maintain intestinal integrity and function when supplemented to the diet of many species. The hypothesis tested here was that glutamine supplementation would overcome the decreased average daily gain (ADG) and altered intestinal morphology caused by milk replacer containing soy protein concentrate (SPC). Holstein calves (9 male and 1 freemartin female per treatment) were assigned to diets of 1) all-milk-protein (from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 31 publications
4
24
0
6
Order By: Relevance
“…In addition, during the first weeks of the calf's life, due to insufficient development of the enzymatic apparatus, there is a low utilization of the nutrients contained in this type of milk replacer thus affecting the animal performance (Davis and Drackley, 1998). The presence of trypsin inhibiting factors and changes in the intestinal flow could have influenced animal's weight (Drackley et al, 2006). The absence of effect in ADG agrees with similar results obtained by Ghorbani et al (2007).…”
Section: ------------------------------------------------------------supporting
confidence: 81%
See 1 more Smart Citation
“…In addition, during the first weeks of the calf's life, due to insufficient development of the enzymatic apparatus, there is a low utilization of the nutrients contained in this type of milk replacer thus affecting the animal performance (Davis and Drackley, 1998). The presence of trypsin inhibiting factors and changes in the intestinal flow could have influenced animal's weight (Drackley et al, 2006). The absence of effect in ADG agrees with similar results obtained by Ghorbani et al (2007).…”
Section: ------------------------------------------------------------supporting
confidence: 81%
“…Because the large market availability of soy, its low cost compared to milk protein and favorable profile of amino acids, it is the most interesting alternative, being widely used for that reason (Davis and Drackley, 1998). Using soy protein concentrates and soy isolates have been able to achieve the requirements of calves; however, the use of these ingredients resulted in lower performance in comparison to whole milk, mainly because of inadequate processing and health problems related to allergic process (Lallès, 2000;Drackley et al, 2006). The lower performance of calves fed with some milk replacers may be associated with the presence of anti-nutritional factors such as trypsin inhibitors, antigenic proteins such as glycine and β-conglycinin, indigestible carbohydrates, lectins, tannins, that are present in some vegetable sources of protein, like soybean (Davis and Drackley, 1998;Chunmei et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Maiorka et al [49], supplementing chickens with 1% L-glutamine, observed an increase of 10.9% in the villous height of the ileum of animals on the seventh day of treatment compared to controls. Drackley et al [50], using a diet containing concentrated soy proteins with 1% L-glutamine, did not observe changes in the villous height in the ileum of calves. Therefore, the 1:100 concentration of L-glutamine administered should be increased, in order to potentially improve the results.…”
Section: Discussionmentioning
confidence: 96%
“…Growth, protein and dry matter digestibility, nitrogen retention, and morphology of the intestinal mucosa of calves on the all milk-protein diet were superior to those of calves on diets containing a soy product . Soy protein contains antigenic and phenolic compounds which adversely affect intestinal integrity and calf growth Drackley et al, 2006). Feeding soy protein supplemented with amino acid diet caused a reduced mucosal protein concentration and a reduced protein: RNA ratio in the jejunum compared with the control diet .…”
mentioning
confidence: 98%
“…Soy protein sources such as soy protein concentrate and soy protein isolate have partly been used in milk replacers (Silva et al, 1986;Drackley et al, 2006). Effects of soyflour in milk replacer on the performance of artificially reared lambs were studied by .…”
mentioning
confidence: 99%